Apoptotic Induction Mechanism of Artonin E in 3D Ovarian Cancer Cell Lines - Abd Rahman, Mashitoh; Mohd Hashim, Najihah (Indonesian Journal of Pharmacy, 2022)
Artonin E is a naturally isolated compound from Artocarpus elasticus and was evaluated for their anticancer property in the present study. This study aimed to develop a 3D ovarian cell culture model and to examine the cytotoxicity of artonin E in 2D and 3D cell culture models. The 3D cell culture was performed using BD™ Puramatrix™ Peptide Hydrogel. Alamar blue assay, selectivity index analysis, morphological apoptotic double staining and immunofluorescence study were conducted to study the antiproliferative and apoptotic induction mechanism of artonin E in 3D SKOV-3 spheroid culture. SKOV-3 cells encapsulated in BD™ Puramatrix™ Peptide Hydrogel clearly demonstrated 3D-spheroid formation. The Alamar blue assay result showed that artonin E inhibited the growth of SKOV-3 cells in 2D and 3D culture with the IC50 values at 72 h treatment of 6.0 ± 0.8 µg/mL and 25.0 ± 0.8 µg/mL, respectively. This compound was found to be less toxic to the normal human ovarian cell lines, T1074, with IC50 values at 72 h of 28.0 ± 0.8 µg/mL in 2D culture and 85.0 ± 0.5 µg/mL in 3D culture, respectively. The selectivity index analysis more than 2 indicated that artonin E was selective against cancer cells compared to normal cells. Artonin E treatment caused apoptotic morphological changes in 3D SKOV-3 spheroids. In a 3D immunofluorescence study, elevated levels of cleaved caspase-3, cleaved caspase-9, apoptotic proteins bax, and decreased levels of antiapoptotic proteins bcl-2, Hsp70, and survivin were observed. In conclusion, artonin E increases chemoresistance and induces cell death in a 3D SKOV-3 spheroids culture via a pro- and anti-apoptotic protein pathway. These findings demonstrate that 3D spheroid culture is an effective platform for testing artonin E therapeutic candidates in an in vivo mimic microenvironment.